2012
DOI: 10.1007/s11682-012-9181-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic imaging of mild traumatic brain injury

Abstract: Traumatic brain injury results in a metabolic cascade of changes that occur at the molecular level, invisible to conventional imaging methods such as computed tomography or magnetic resonance imaging. Non-invasive metabolic imaging tools such as single photon emission computed tomography (SPECT), positron emission tomography (PET), and magnetic resonance spectroscopy (MRS) are the ideal methods for providing insight to these changes by measuring regional cerebral blood flow, glucose metabolism, and brain metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(138 citation statements)
references
References 48 publications
3
135
0
Order By: Relevance
“…NAA has been extensively studied in mTBI, either in absolute amounts or in ratios to Cr and Cho. Decreases in any of these three values, usually interpreted as neuronal injury, have been recorded throughout the gray matter and WM, in specific regions, as well as globally (149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159)(160). Some of these findings have shown correlations with postconcussive symptoms (156,159), as in a recent study that found lower global WM NAA only in symptomatic patients (Fig 7) (161).…”
Section: Metabolic Alterations: Proton Mr Spectroscopy and A Brief Nomentioning
confidence: 62%
See 1 more Smart Citation
“…NAA has been extensively studied in mTBI, either in absolute amounts or in ratios to Cr and Cho. Decreases in any of these three values, usually interpreted as neuronal injury, have been recorded throughout the gray matter and WM, in specific regions, as well as globally (149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159)(160). Some of these findings have shown correlations with postconcussive symptoms (156,159), as in a recent study that found lower global WM NAA only in symptomatic patients (Fig 7) (161).…”
Section: Metabolic Alterations: Proton Mr Spectroscopy and A Brief Nomentioning
confidence: 62%
“…This is consistent with the view that in mTBI, as opposed to more severe injuries, there is less cell-membrane breakdown, which would release 1 H MR spectroscopically detectable Cho. In the chronic TBI stages, however, any Cho elevations are likely to reflect glial proliferation (160). Time from injury, therefore, should be taken into account when discussing changes in Cho, while in the interpretation of the NAA/Cho ratio, possible Cho increases (149,167), as well as decreases (166), should be considered.…”
Section: State Of the Art: Mr Imaging Applications In Mild Traumatic mentioning
confidence: 99%
“…Although both MRS and MRI exploit the spin-relaxation properties of protons, MRI uses this information to create a 2D image of the brain, whereas MRS determines the relative concentrations of various brain metabolites. 74 In a study of 11 former professional soccer players, MRS revealed a significant increase in choline (a marker for cellular proliferation and tissue damage) and myoinositol (a glial activation marker) compared with age-matched controls. 68 No neurocognitive deficits were reported in this study group.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…24,25 In two longitudinal studies in which patients were scanned 3 or 4 times to perform the time course of postinjury recovery of brain metabolism, we showed that concussion, an mTBI caused by any type of acceleration-deceleration of the brain, frequently encountered in contact sports, caused a reversible decrease in NAA content of the frontal lobe white matter. 26,27 In these studies, an inclusion criterion was the constancy in the Cho/Cr ratio that allowed the semiquantitative determination of NAA relative to both Cr and Cho.…”
mentioning
confidence: 90%